Ghost plane : the true story of the CIA torture program - Grey, Stephen, 1968- (New York : St. Martin's Press, 2006)
Investigative journalist Grey tells the inside story of international prisons sanctioned by the U.S. Government and used by the CIA to hold and torture people suspected of terrorism. He takes an unflinching look at a practice that scorns Geneva Convention rules and is powered by corruption at the highest levels of governments worldwide-- individuals abducted at airports around the world and transported for interrogation and torture on planes manned by CIA operatives. Using contacts deep inside the government, Grey paints a disturbing ethical picture of the war on terror as he reveals how deeply the Bush administration is involved in the program and questions the truth of statements made by Secretary of State Condoleeza Rice. He also shines a spotlight on the heads of European nations who turned a blind eye to the program when it showed up in their back yards.--From publisher description.
Includes bibliographical references (p. [313]-364) and index.
Keywords: United States. -- Central Intelligence Agency; Torture -- United States -- History; Intelligence service -- United States